PHYSIOLOGICAL EFFECTS OF PROFENOFOS INSECTICIDE TOWARDS CONSUMPTION RATE 6 AND ASSIMILATION EFFICIENCY OF COW – DUNG BY EARTHWORMS 7 PONTOSCOLE CORETHRURUS FR. MULL - Nofyan, Erwin; Kamal, Mustafa; Lamin, Syafrina; Rahmasari, Indah (BIOVALENTIA: Biological Research Journal, 2020)
The purpose of this research is to determined the effect of insecticide profenofos to the rate of consumption and assimilation efficiency of cow- dung by earthworms Pontoscolex corethrurus Fr. Mull. This research used Completely Randomized Design with 6 treatments and 5 repetition. Treatments that was given to sample are the insecticide profenofos with concentration of 0 % (control); 0.1%; 0.2 %; 0.3 %; 0.4 %; 0.5 %. Data analysis was using Varians Analysis. If there was real difference then data analysis continued with The Duncan Test on level of confidence of 95%. The results of this research show us that several concentration of insecticide carbaryl have the real effect to the average of consumption rate and the efficiency of absorption. The lowest average of consumption rate on earthworm Pontoscolex corethrurus Fr.Mull is on concentration of 0.5 % (0.23 ± 0.02 mg/g day) and the highest average of consumption 26 rate on earthworm Pontoscolex corethrurus Fr. Mull is on concentration of 0% (control) (2.53 ± 0.05 mg/g day). The lowest average of approach digestyon earthworm Pontoscolex corethrurus is on concentration of 0 % (control) (40.78 28 ± 2.56 %) and the highest average of digestion earth worm Pontoscolex corethrurus Fr.Mull is on concentration of 0.5 % 29 (70.76 ± 3.67 %).